Development of Three-Tier Diagnostics Instruments on Students Misconception Test in Fluid Concept - Irwansyah, Irwansyah; Sukarmin, Sukarmin; Harjana, Harjana (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2018)
The purpose of this research was to know the validity and reliability of instrument three-tier diagnosis to identify the students’ misconception in fluid concept. The stages of development research that used in this research were (1) The first research and collecting information, (2) planning and designing of development (3) validity and product evaluation. The instrument of the test was tested on 98 students of 3 schools. The instrument has been developed and categorized effectively because it has a valid category with the Aiken validity index value> from table V (0.75) and the reliability of the instrument has a value of 0.96 with a high category. The instrument of three-tier test that developed was able to identify the students' comprehension in students' concept and students' misconception. There are 27,58% students comprehend the concept, 45,29% students did not comprehend the concept, 24,74% students showed that misconception and 2,36% students experienced errors